Penerapan Terapi Musik Klasik Pada Pasien Skizofrenia dengan Halusinasi Pendengaran Dalam Menurunkan Tanda dan Gejala Halusinasi di Prima Harapan Bandung - Nurmarisa, Ivena; Siti Fauziah Yani, Fifi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: Schizophrenia is a severe and persistent neurobiological brain disease. One of the symptoms of schizophrenia is hallucinations. Hallucinations are sensory perception disorders that occur in the absence of a real stimulus from the five senses, and it is often difficult to distinguish between reality and the unreal. Schizophrenia sufferers with auditory hallucinations need good treatment to control themselves from the impacts that will occur. Music therapy is a therapy that is often done because it is very easily accepted by the hearing. Music can affect imagination, intelligence, and memory, and can affect the pituitary in the brain to release endorphins. Music that produces alkaline effects is typically soft classical music, which makes it relaxing and calming. Objective: to provide nursing care by applying classical music therapy to schizophrenia patients with auditory hallucinations. Method: The method used is a descriptive method with a case study approach while the data collection process is through interviews and observations. Results: The results obtained after being given classical music therapy for 3 days which was done once a day for 15 minutes showed a decrease in signs and symptoms of hallucinations from 55% to 0%. Conclusion: The application of classical music therapy is effective in reducing the signs and symptoms of auditory hallucinations.